PENGARUH PENGGUNAAN MEDIA VIDEO REKAM LAYAR TERHADAP KEMAMPUAN BELAJAR PROPOSAL KELAS XI DI SMK NEGERI 2 WONOGIRI - FITRI ITUT RAHAYU (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
Distance Learning during the current Covid-19 pandemic causes various problems, one of which is the lack of understanding of students towards learning materials. Due to the limited access to face-to-face with educators in Indonesian language lessons, the level of understanding of 11th grade students of SMKN 2 Wonogiri in the 2020-2021 school year class in the proposal material is still lacking. Learning Indonesian in the proposal chapter is a fairly difficult chapter so it requires sufficient explanation so that students better understand the details of learning. Students' understanding of the proposal is minimal, making it difficult for students to understand and study the proposal. One of the focus problems behind this is the lack of variety of Indonesian language learning media in the implementation of Distance Learning during the pandemic. For this reason, a new breakthrough is needed in the use of more innovative and effective media adapted to the distance learning model of Indonesian language subjects. The media used is screen recording video media. The purpose of this study was to describe the effect of using screen recording video media on the ability to study proposals for 11th grade students of SMKN 2 Wonogiri in the 2020-2021 school year class and to describe the magnitude of the effect of using screen recording video media on popular learning abilities. 11th grade students of SMKN 2 Wonogiri in the 2020-2021 school year class. The method used in this study is a quasi-experimental type with the Nonequivalent Control Group Design type. The data collection used by the researcher is tests, observations, and documentation. The conclusion of this study is that the use of screen recording video media in distance learning has a positive influence on the ability to study proposals. ABSTRAKPembelajaran Jarak Jauh di masa pandemi Covid-19 saat ini menimbulkan berbagai masalah, salah satunya adalah kurangnya pemahaman peserta didik terhadap materi pembelajaran. Karena terbatasnya akses tatap muka dengan pendidik dalam pelajaran bahasa Indonesia, tingkat pemahaman peserta didik kelas XI SMK Negeri 2 Wonogiri dalam materi proposal masih kurang. Pembelajaran bahasa Indonesia dalam bab proposal adalah bab yang cukup sulit sehingga butuh penjelasan yang cukup agar peserta didik lebih memahami detail pembelajaran. Pemahaman peserta didik terhadap proposal sangat minim sehingga menyulitkan peserta didik dalam memahami dan mempelajari proposal. Salah satu fokus permasalahan yang melatarbelakangi hal tersebut adalah kurang variatifnya media pembelajaran bahasa Indonesia dalam pelaksanaan Pembelajaran Jarak Jauh di masa pandemi. Untuk itu diperlukan terobosan baru dalam penggunaan media yang lebih inovatif dan efektif disesuaikan dengan model pembelajaran jarak jauh mata pelajaran bahasa Indonesia. Media yang digunakan adalah media video rekam layar. Tujuan dari penelitian ini adalah untuk mendeskripsikan pengaruh penggunaan media video rekam layar terhadap kemampuan belajar proposal peserta didik kelas XI SMK Negeri 2 Wonogiri serta mendeskripsikan besarnya pengaruh penggunaan media video rekam layar terhadap kemampuan belajar poposal peserta didik kelas XI SMK Negeri 2 Wonogiri. Metode yang digunakan dalam penelitian ini adalah jenis eksperimen semu dengan tipe Nonequivalent Control Group Design. Pengumpulan data yang digunakan peneliti adalah tes, observasi, dan dokumentasi. Simpulan penelitian ini adalah bahwa penggunaan media video rekam layar dalam pembelajaran jarak jauh ini memberikan pengaruh positif terhadap kemampuan belajar proposal.